Perbandingan Algoritma Sequential Search dan Binary Search Pada Website E-Tracking Pengajuan Surat - Avilla, Beby; Fauziah, Fauziah; Winarsih, Winarsih (Jurnal Informatika: Jurnal Pengembangan IT, 2024)
Disposition of a letter is an action taken in response to receiving a letter which is usually of an urgent nature or which must be carried out or followed up immediately. In an agency or organization, the flow of disposition letters usually begins with an incoming letter addressed to superiors or leaders. Based on the problems that occurred in Cilangkap Village, where after submitting letters, residents often felt confused about the disposition of the letters they submitted because there was no information regarding the disposition of computerized letters. This study aims to build a website-based letter submission information system and e-tracking letter disposition to make it easier for residents to know the disposition of their letter. This study uses the Sequential Search Algorithm and the Binary Search Algorithm to find the average time needed to search data using the microtime function and obtain the most optimal results from the two algorithms. The results showed that from a total of 507 data, 100 data searches for letter submissions obtained the average result of the Sequential Search Algorithm search time is 5.35 miliseconds and the Binary Search Algorithm is 6.16 miliseconds. So from the research results it can be seen that the Sequential Search Algorithm is more efficient and optimal in the search for letter submission data.